2003
DOI: 10.1161/01.hyp.0000047511.97879.fc
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Linked Hypertension in Offspring of Lard-Fed Pregnant Rats

Abstract: Abstract-Epidemiological studies suggest an association between maternal nutrition and offspring cardiovascular disease.We previously demonstrated endothelial dysfunction and abnormal aortic fatty acid composition in adult female offspring of rats fed animal lard during pregnancy. We have now further investigated this model. Female Sprague-Dawley rats were fed a control breeding diet (5.3% fat) or a diet rich in lard (25.7% fat) 10 days before and throughout pregnancy and lactation. Male and female offspring w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
318
1
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(350 citation statements)
references
References 44 publications
23
318
1
8
Order By: Relevance
“…While we cannot categorically state that the difference in age did not contribute to the sex-related difference observed in insulin resistance, our recent report on the offspring of obese mice [42] also showed that glucose intolerance was predominantly observed in males. Moreover, we have also previously shown a male predominance of insulin resistance in adult offspring of rats fed a lard-rich diet [49]. Also, there was a marginally significant difference in insulin resistance in males, but not in females at 3 months.…”
Section: Discussionsupporting
confidence: 53%
“…While we cannot categorically state that the difference in age did not contribute to the sex-related difference observed in insulin resistance, our recent report on the offspring of obese mice [42] also showed that glucose intolerance was predominantly observed in males. Moreover, we have also previously shown a male predominance of insulin resistance in adult offspring of rats fed a lard-rich diet [49]. Also, there was a marginally significant difference in insulin resistance in males, but not in females at 3 months.…”
Section: Discussionsupporting
confidence: 53%
“…On the contrary, feeding a diet rich in lard to pregnant rats also affected systolic blood pressure in adult offspring, even if fed a normal diet, but the female offspring were more sensitive than the male to this foetal nutrition-induced hypertension. 12 These results could be related to the saturated/polyunsaturated fatty acid ratio in endothelium, since it was shown that a saturated diet in rat increases catecholamine sensitivity and decreases endothelium-dependent relaxation mesenteric arteries. 13 Some epidemiological studies including a 'saturated fat' arm have focused on cholesterol, circulating lipids, atherosclerosis, coronaropathies and stroke, but not on blood pressure.…”
Section: Hypertension and Sfamentioning
confidence: 99%
“…Premenopausal women have lower arterial blood pressure than men matched for age and post-menopausal women, suggesting a role of ovarian hormones in blood pressure regulation [71]. In rats, feeding a diet rich in lard to pregnant females leads to gender-related cardiovascular dysfunction in normally fed offspring as blood pressure was found to be high in the female but not in the male offspring [72]. A maternal low-protein diet (LPD) during pregnancy and lactation modifies the growth and metabolism of the progeny (F2) of the female offspring (F1) [73,74].…”
Section: Sexual Dimorphism In Consequences On Offspringmentioning
confidence: 99%